The Evolving Role of Radiation Therapy in the Treatment of Biliary Tract Cancer - Gkika, Eleni; Hawkins, Maria A.; Grosu, Anca-Ligia; Brunner, Thomas B. (Frontiers in Oncology, 2020)
Biliary tract cancers (BTC) are a disease entity comprising diverse epithelial tumors, which are categorised according to their anatomical location as intrahepatic (iCCA), perihilar (pCCA), distal (dCCA) cholangiocarcinomas and gallbladder carcinomas (GBC), with distinct epidemiology, biology and prognosis(Rizvi et al., 2018). Complete surgical resection is the mainstay in operable BTC as it is the only potentially curative treatment option. Nevertheless, even after curative (R0) resection, the 5-year survival rate ranges between 20-40% and the disease free survival rates (DFS) is approximately 48 to 65% after one year and 23 to 35% after three years without adjuvant treatment (Takada et al., 2002;Tamandl et al., 2008;Choi et al., 2009). Improvements in adjuvant chemotherapy have improved the DFS (Lamarca et al., 2020) but the role of adjuvant radiotherapy is unclear. On the other hand more than 50% of the patients present with unresectable disease at the time of diagnosis, which limits the prognosis to a few months without treatment. Herein, we review the role of radiotherapy in the treatment of cholangiocarcinoma in the curative and palliative setting.